2014
DOI: 10.3390/md12010462
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Biochemical Characterization of Halisulfate 3 and Suvanine as Novel Inhibitors of Hepatitis C Virus NS3 Helicase from a Marine Sponge

Abstract: Hepatitis C virus (HCV) is an important etiological agent that is responsible for the development of chronic hepatitis, liver cirrhosis, and hepatocellular carcinoma. HCV nonstructural protein 3 (NS3) helicase is a possible target for novel drug development due to its essential role in viral replication. In this study, we identified halisulfate 3 (hal3) and suvanine as novel NS3 helicase inhibitors, with IC50 values of 4 and 3 µM, respectively, from a marine sponge by screening extracts of marine organisms. Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…A fluorescence helicase assay based on FRET [ 26 , 27 ], with modifications in the fluorescent dyes, was used to examine NS3 helicase inhibition by different compounds. Since hydroxyanthraquinone is known to exhibit a wide range of absorption wavelengths in aqueous solution, ranging from shorter to longer wavelengths (e.g., ~200 up to 700 nm) [ 28 ], we used a dsRNA substrate prepared by annealing the 5′ Alexa Fluor 700 (maximum excitation/emission = 702/723 nm)-labeled fluorescence strand to the 3′ Black Hole Quencher (BHQ)-3-labeled quencher strand with the same RNA sequences, as described in previous reports [ 27 , 29 ], to avoid interference due to hydroxyanthraquinone absorption. The concentration of the capture strand was optimized to 400 nM based on the Z ′ value [ 30 ]; the Z ′ value validates assay conditions as having reliability and reproducibility when its value is close to 1.…”
Section: Resultsmentioning
confidence: 99%
“…A fluorescence helicase assay based on FRET [ 26 , 27 ], with modifications in the fluorescent dyes, was used to examine NS3 helicase inhibition by different compounds. Since hydroxyanthraquinone is known to exhibit a wide range of absorption wavelengths in aqueous solution, ranging from shorter to longer wavelengths (e.g., ~200 up to 700 nm) [ 28 ], we used a dsRNA substrate prepared by annealing the 5′ Alexa Fluor 700 (maximum excitation/emission = 702/723 nm)-labeled fluorescence strand to the 3′ Black Hole Quencher (BHQ)-3-labeled quencher strand with the same RNA sequences, as described in previous reports [ 27 , 29 ], to avoid interference due to hydroxyanthraquinone absorption. The concentration of the capture strand was optimized to 400 nM based on the Z ′ value [ 30 ]; the Z ′ value validates assay conditions as having reliability and reproducibility when its value is close to 1.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the biological activities of the sulfated sestertepenoids mentioned above, two individual studies on the biological activity of the crude extracts of marine organisms revealed that suvanine is responsible for the high activity of some sponge extracts against hepatitis C virus NS3 helicase (Furuta et al 2014) and adenosine A1 receptor (Ali et al 2013), respectively. It was also found that suvanine effectively antagonize the mammalian bile acid sensor farnesoid X receptor, which resulted in the discovery of molecular bases of the antagonism and more potent semi-synthetic derivatives (Di Leva et al 2013).…”
Section: Introductionmentioning
confidence: 98%
“…For characterization of the inhibitory mechanism, radioactive assays that evaluate the ATPase and RNA-binding activities of NS3 are employed [18][19][20][21][22][23], because these activities are linked to helicase activity and are well-known targets of HCV NS3 helicase inhibitors [24].…”
Section: Methodsmentioning
confidence: 99%
“…Alternatively, the gel-based assay can be performed with a double-stranded substrate labeled with a single fluorophore (such as Alexa Fluor 488) [23]. The fluorescent signal from the fluorophore-labeled dsRNA can be visualized using a fluorescent gel scanner, such as a Typhoon 9210 imager (GE Healthcare).…”
Section: Notesmentioning
confidence: 99%
See 1 more Smart Citation